Systemic Dissemination of Injected Foreign Material. Issue 4 (4th December 2018) - Olds, Kelly; Gilbert, John; Langlois, Neil E.I.; Byard, Roger W.
Abstract: A 32‐year‐old woman collapsed following an intravenous injection of material that included crushed pharmaceutical tablets. Resuscitation was attempted but was unsuccessful. She had an extensive past medical history of complications resulting from intravenous drug use. Death was due to mixed drug toxicity. The major findings at autopsy included a 10 mm deep skin sinus over the right femoral vein that was used as an injection site. Polarizable foreign material was present at the injection site and also within the lungs with a granulomatous reaction. Of note, a probe‐patent foramen ovale had permitted paradoxical embolization of this material into the systemic circulation with lodgement within the liver, portal lymph nodes, myocardium, spleen, kidneys, and pancreas. This case highlights the importance of checking for any intracardiac shunts, which may be quite small, and systemic dissemination of foreign material to multiple organs in intravenous drug users who present for medicolegal assessment.